Development of a new bioactivatable fluorescent probe for quantification of apolipoprotein A-I proteolytic degradation in vitro and in vivo. (March 2017) - Maafi, Foued; Li, Baoqiang; Gebhard, Catherine; Brodeur, Mathieu R.; Nachar, Walid; Villeneuve, Louis; Lesage, Frédéric; Rhainds, David; Rhéaume, Eric; Tardif, Jean-Claude
Abstract: Background and aims: The potential benefits of high-density lipoproteins (HDL) against atherosclerosis are attributed to its major protein component, apolipoprotein A-I (apoA-I). Most of the apoA-I in the vascular wall appears to be in its lipid-poor form. The latter, however, is subjected to degradation by proteases localized in atherosclerotic plaques, which, in turn, has been shown to negatively impact its atheroprotective functions. Here, we report the development and in vivo use of a bioactivatable near-infrared full-length apoA-I-Cy5.5 fluorescent probe for the assessment of apoA-I-degrading proteolytic activities. Methods: Fluorescence quenching was obtained by saturation of Cy5.5 fluorophore molecules on apoA-I protein. ApoA-I cleavage led to near-infrared fluorescence enhancement. In vitro proteolysis of the apoA-I probe by a variety of proteases including serine, cysteine, and metalloproteases resulted in an up to 11-fold increase in fluorescence ( n  = 5, p  ≤ 0.05). Results: We detected activation of the probe in atherosclerotic mice aorta sections using in situ zymography and showed that broad-spectrum protease inhibitors protected the probe from degradation, resulting in decreased fluorescence (−54%, n  = 6 per group, p  ≤ 0.0001). In vivo, the injected probe showed stronger fluorescence emission in the aorta of human apoB transgenic Ldlr − /− atherosclerotic mice (ATX) as compared to wild-type mice. In vivo observations were confirmed by ex vivo aorta imaging quantification where a 10-fold increase in fluorescent signal in ATX mice ( p  ≤ 0.05 vs. control mice) was observed. Conclusions: The use of this probe in different applications may help to assess new molecular mechanisms of atherosclerosis and may improve current HDL-based therapies by enhancing apoA-I functionality. Highlights: Most of the apoA-I in the vascular wall may occur in its lipid-poor form. Proteases localized in atherosclerotic plaques can degrade apoA-I. Saturation of apoA-I by Cy5.5 fluorophore lead to a quenched fluorescence probe. ApoA-I-Cy5.5 probe proteolytic cleavage increase its fluorescence emission. ApoA-I-Cy5.5 probe allow the detection of protease activities that degrade apoA-I.